Doxorubicin conjugated quantum dots to target alveolar macrophages/inflammation - Chakravarthy, Krishnan V. (2010)
The ability to provide targeted therapeutic delivery in the lung would be a major advancement in pharmacological treatments for many pulmonary diseases. Critical issues for such successful delivery would require the ability to target specific cell types, minimize toxicity (i.e. inflammatory response) and to deliver therapeutic levels of drugs. We report here on the ability of nanoconjugates of CdSe/CdS/ZnS Quantum Dots (QDs) and doxorubicin (Dox) to target alveolar macrophages cells (aMØ), which play a critical role in the pathogenesis of inflammatory lung injuries. Confocal imaging showed the release of Dox from the QD-Dox nanoconjugate, as was evident by its accumulation in the cell nucleus and induction of apoptosis, suggesting that the drug retains its bioactivity after coupling to the nanoparticle. Inflammatory injury parameters (albumin leakage, proinflammatory cytokines and neutrophil infiltration) were recorded after in vivo admistration of QD-Dox and Dox observing no significant effect after QD-Dox treatment compared with Dox. These results demonstrate that nanoparticle platforms can provide targeted macrophage-selective therapy for the treatment of pulmonary disease.